AST1-4,6-10 (Architectural As Built Drawings) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2024)
This record contains architectural as built drawings of Brac University New Campus Project. It consists of both PDF & DWG version of drawings.